PENGEMBANGAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM KURIKULUM MERDEKA - Nursiah; Dwi Ratnasari; Yanto Bashri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to study and perfect the independent curriculum for learning Islamic Religious Education. The Merdeka Curriculum is an effort to improve the quality of PAI education to give schools, teachers and students the freedom to in- novate, learn independently and creatively, with a focus on meaningful learning without the pressure of achieving certain grades. This research uses the library study method or library research, which is a type of research carried out by collect- ing information from various written sources such as books, articles and other ref- erences. The results of this research are that the independent curriculum in PAI learning is expected to encourage students to think critically and be relevant to the times. PAI teachers need to understand learning outcomes and formulate learning objectives according to the level and stage of students. The implementation of the independent curriculum in PAI focuses on faith, piety, skills and noble morals, as well as facing the challenges of the globalization era by preparing graduates who are competent and have noble values. However, the abundant growth of human resources, the character of education, and the paradigm are less appropriate in understanding the curriculum. By overcoming these challenges, it is hoped that the Merdeka Curriculum can advance Islamic education towards graduates who are competent, have noble character, and are able to compete in the era of technolog- ical progress.